HIILIRISASI DAYA SAING DAN POTENSI PENGEMBANGAN PASAR PRODUK KARET INDONESIA DI NEGARA ASEAN5 - Zainuddin Zainuddin (Universitas Batangahari Jambi, 2020)
The increase in exports of Indonesian rubber products is the key to the success of the rubber product downstream policy to gain added value and foreign exchange. The export market for rubber products in ASEAN5 is competing with similar products from East Asia. As an exporter, Indonesia must focus on strengthening competitiveness and exploiting the potential market in ASEAN5.The purpose of this article is to describe the competitiveness and development potential of the Indonesian rubber product market in ASEAN5 countries (Singapore, Malaysia, Thailand, Vietnam, the Philippines). The analysis that describes the competitiveness of Indonesian rubber products uses the RCA method and market share. Analysis of the position and potential for market development of Indonesian rubber products using the Export Product Dynamic method. The competitiveness of Indonesian rubber products in ASEAN5 markets is quite varied. Indonesian rubber products have a relatively strong competitiveness value in the Singapore market, but weak in other ASEAN5 markets such as Malaysia, Thailand, the Philippines and Vietnam. Indonesian rubber products compete fiercely with similar industries in importing countries and major competitors from East Asia (China, Japan, South Korea). The clusterization shows that Indonesian rubber products have a potential market in Thailand, although their competitiveness is relatively weak but in a rising star market position. The market potential in Singapore and the Philippines is less potential, but has relatively strong competitiveness in Singapore and a falling star market position in the Philippines. Indonesian rubber products have no potential in Malaysia and Vietnam.